2016
DOI: 10.18632/oncotarget.12154
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive meta-analysis of genetic associations between five key SNPs and colorectal cancer risk

Abstract: Genome-wide association studies (GWAS) on colorectal cancer (CRC) have identified dozens of single nucleotide polymorphisms (SNPs) in more than 19 independent loci associated with CRC. Due to the heterogeneity of the studied subjects and the contrary results, it is challenging to verify the certainty of the association between these loci and CRC.We conducted a critical review of the published studies of SNPs associated with CRC. Five most frequently reported SNPs, which are rs6983267/8q24.21, rs4939827/18q21.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…[ 61 ] was carried out in Caucasians, while it was incorporated into the Asian subgroup in a previous meta-analysis [ 17 ]; 2) we included 7 case-control studies in Asians, instead of only 4 studies in a meta-analysis by Haerian et al . [ 18 ], and therefore, results of our meta-analysis were more credible; 3) lack of further research in different stratified analyses prevented comprehensive understanding in a recent meta-analysis [ 21 ]; 4) our results were based on sufficient evidence, which was proved by FPRP for the first time.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[ 61 ] was carried out in Caucasians, while it was incorporated into the Asian subgroup in a previous meta-analysis [ 17 ]; 2) we included 7 case-control studies in Asians, instead of only 4 studies in a meta-analysis by Haerian et al . [ 18 ], and therefore, results of our meta-analysis were more credible; 3) lack of further research in different stratified analyses prevented comprehensive understanding in a recent meta-analysis [ 21 ]; 4) our results were based on sufficient evidence, which was proved by FPRP for the first time.…”
Section: Discussionmentioning
confidence: 88%
“…Besides, such contradictions also existed in some other meta-analyses [ 17 – 19 ]. Of note, lack of further evaluation in different stratified analyses prevented comprehensive understanding in some recent meta-analyses [ 20 , 21 ]. To better understand the precise relationship, we performed a comprehensive meta-analysis with increased statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…These independent whole genome‐wide association studies both found loci on 10p14 to be commonly associated with CRC. We consider this 10p14 locus to be a significant region of CRC susceptibility because it was identified in multiple studies in more than one race, including European and Japanese populations . Recently, a significant interaction between an SNP at 10p14 (rs4143094) and processed meat consumption was also reported in CRC patients …”
Section: Discussionmentioning
confidence: 99%
“…We consider this 10p14 locus to be a significant region of CRC susceptibility because it was identified in multiple studies in more than one race, including European and Japanese populations. (29,30) Recently, a significant interaction between an SNP at 10p14 (rs4143094) and processed meat consumption was also reported in CRC patients. (31) We performed data mining for genes that exist in this susceptibility locus in order to investigate the mechanism by which these SNP are connected to the causes of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…If there is no significant heterogeneity, the pooled OR is calculated by a fixed effect model; otherwise by a random-effect model [1517, 2830, 3541]. Z test is used to determine the significance of pooled OR [2830].…”
Section: Methodsmentioning
confidence: 99%